Common cellular and molecular mechanisms and interactions between microglial activation and aberrant neuroplasticity in depression. (15th December 2020) - Guo, Xiaoyun; Rao, Yanxia; Mao, Ruizhi; Cui, Lvchun; Fang, Yiru
Abstract: It has been suggested that inflammation is involved in the pathophysiology of depression. As tissue-specific macrophages in the central nervous system (CNS), microglia play an important role in neuroinflammation. Resident microglia become activated towards the pro-inflammatory (M1) phenotype or the anti-inflammatory (M2) phenotype during neuroinflammation. In the CNS, neurons report to microglia regarding their statuses and can regulate microglial activation, while microglia also modulate neuronal activities, including neuroplasticity. The molecular mechanisms underlying the communication between microglia and neurons, which include intracellular and extracellular signalling pathways, might be complex and of great importance for new research on the pathogenesis of depression. The present review aims to discuss the common cellular and molecular mechanisms for microglial activation and aberrant neuroplasticity in depression and the role of these processes in the pathogenesis of depression. Highlights: Inflammation is involved in the pathogenesis of depression. Microglial activation and aberrant neuroplasticity contribute to the pathogenesis of depression. Cellular and molecular mechanisms for microglial activation and aberrant neuroplasticity in depression.